A prolonged red tide of Heterocapsa triquetra (Ehrenberg) F. Stein (Dinophyceae) and phytoplankton succession in a eutrophic estuary in Turkey - TAS, S. (Mediterranean Marine Science, 2015)
A prolonged red tide of Heterocapsa triquetra and phytoplankton succession were investigated in a eutrophic estuary (Golden Horn) for a year. Runoff following the rainfall in winter supplied high amounts of nutrients and also created a mesohaline frontal zone in the middle and upper estuary. Red tide of H. triquetra was first observed with an orange-brownish water discoloration at the upper estuary in January. Highest cell density of H. triquetra was 2.7×106 cells l-1 in January and reached to 19.2×106 cells l-1 in April. Successive blooms continued with dinoflagellate Prorocentrum minimum in May and phytoflagellates Eutreptiella marina and Fibrocapsa sp. in summer. High chl-a and dissolved oxygen were measured in the spring depending on algal biomass. Findings indicate that H. triquetra might be adapted to moderate salinity and low temperatures and red tide events should be considered as a response to increasing eutrophication due to high amounts of nutrients. Eutrophication can lead to harmful algal blooms for this area in the near future.